PROSPECT FOR CO2 EOR TO OFFSET THE COST OF CCS AT COAL POWER PLANTS - Usman Usman (Scientific Contributions Oil and Gas, 2016)
Carbon Capture Storage (CCS) technology has gained confi dence in its ability to yield dramatic reductions of CO2 emissions from large stationary emissions sources such as coal-fi red power plants. However, the pace of CCS projects has suffered from a less supportive business case. Utilization of CO2 for enhanced oil recovery (CO2 EOR) offers commercial opportunities owing to its economic profi tability from incremental oil production offsetting the cost of CCS. This paper describes the prospect of CO2 EOR offsetting the cost of CCS at a coal-fi red power plant. A coal-fi redpower plant assumed to be commissioned in 2022 is selected as the basis of this study. The Levelized Cost of Electricity (LCOE) of this plant without CCS is estimated at US$ 6.4 cents/kWh and emits around 4.1 MtCO2 /year. Integrating CCS to the selected coal power plant imposed additional costs associated with CO2 capture, transportation, and storage systems. The incremental costs are evaluated based on separation of 90%, 45%, and 22.5% of CO2 from the power plant fl ue gas. Under the 90% capture scenario, the LCOE raised more than double to 15.5 US cents/kWhÂ which is primarily attributed to the energy penalty. A minimal reduction of 0.9 cents/kWh could bring the LCOE down below the ceiling price for geothermal. Reducing the CO2 capture percentage from 90% to 45% could reduce the LCOE to 11.2 US cents/kWh. Lowering the cost to 0.6 cents/kWh or more for this case would result in the LCOE below the state-owned electricity companyâ€™s average cost of combined cycle gas turbine in 2012. Selling the captured CO2 under US$ 10 per tonne at the plant gate could help offset the cost. With numbers of new coal-fi red power plants expected to be constructed in the near term, integrated coal CCS power plant with EOR is relevant for Indonesia.